HAEMATOLOGY AND SERUM BIOCHEMISTRY PARAMETERS AS INDICATORS OF THE MOST COMMON CANINE VECTOR BORNE DISEASES IN RN MACEDONIA - Atanaskova Petrov; Novakov, Todor; Celeska Irena (Faculty of Veterinary Medicine, University of Forestry, Sofia, Bulgaria, 2022)
Canine vector borne diseases (CVBD) are one of the major health issues in Macedonia, with potentially fatal outcome if not treated in time. The diseases are caused by different pathogenic organisms (e.g. bacteria, protozoa, helminths), transmitted by various blood sucking arthropod vectors. Most commonly present CVBD in Macedonia are ehrlichiosis (caused by Ehlrlichia canis), heartworm disease (Diroffilaria immitis), anaplasmosis (Anaplasma platys and phagocytophilum) and leishmaniasis (Leiishmania infantum). Infected dogs can present variety of clinical signs, depending of the stage of the disease and the affected organs. The aim of this study was to present most commonly found haematology and serum biochemistry alterations in dogs with ehrlichiosis, anaplasmosis, heartworm or leishmaniosis. For that purpose, we analysed 40 dogs, divided in 4 groups (each group contained 10 dogs), depending of the disease. Haematology (RBC, PCV, HGB, WBC, and PLT) and serum biochemistry analyses (ALT, AST, ALKP, albumin, total protein, globulin, urea and creatinine) were analysed for each dog. The results revealed moderate normocytic normochromic anaemia (PCV 17.82%, ±4.5, HGB 8.3 g/dl ±2.29) with elevated kidney parameters (Urea 30.7 mmol/l ±20.41 and creatinine 352.62 μmol/l ± 274.12) as well as hypoalbuminemia (18.48 mmol/l±6.96) and hyperglobulinemia (37.13 mmol/l ±7.16) in patients with leishmaniasis. Thrombocytopenia (PLT 95.4*10-9/l±97.39) was marked haematology parameter for patients with ehrlichiosis, while elevated ALKP (302.57 U/l ±73.15) was present in dogs with heartworm disease. These laboratory parameters can be used in conjunction with the clinical findings as indicators for further necessary diagnostic tests for CVBD in dogs.
Keywords: canine vector borne disease, hematology, serum biochemistry